2010
DOI: 10.1177/1084822310384694
|View full text |Cite
|
Sign up to set email alerts
|

Predicting In-Home Respite Utilization by Family Caregivers of Older Adults: Results of a Community Study

Abstract: This longitudinal study applies the behavioral model of health services use (Andersen, 1995) to the prediction of in-home respite utilization within the naturalistic context of ongoing respite services. Participants (N = 74) were family caregivers who provided informal care for a physically and/or cognitively impaired older adult. All participants resided in the Midwest and received in-home respite services managed by an Area Agency on Aging and funded through the National Family Caregiver Support Program. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…However, we can learn more about our FCG participants from the dataset to contribute to the literature on caregivers of older adults. Confirmation of the existence of broad‐based differences in the care giving experience (by virtue of factors such as relationship, age, sex, race, ethnicity, health, and socioeconomic status) substantiates the need for more research and related theories to explain the differential effects of these important variables (e.g., see Haley, Roth, Howard, & Safford, 2010; Mensie & Steffen, 2011; Wang, Shyu, Chen, & Yang, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…However, we can learn more about our FCG participants from the dataset to contribute to the literature on caregivers of older adults. Confirmation of the existence of broad‐based differences in the care giving experience (by virtue of factors such as relationship, age, sex, race, ethnicity, health, and socioeconomic status) substantiates the need for more research and related theories to explain the differential effects of these important variables (e.g., see Haley, Roth, Howard, & Safford, 2010; Mensie & Steffen, 2011; Wang, Shyu, Chen, & Yang, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…The original framework proposed by Andersen and Newman was expanded over time, incorporating need, predisposing and enabling factors of the primary caregiver, and informal family support to explain use of long-term care (Bass & Noelker, 1987). The importance of caregiver factors in explaining the use of LTC was confirmed and emphasized by other studies (Bookwala et al, 2004;Buhr, Kuchibhatla, & Clipp, 2006;Caron, Ducharme, & Griffith, 2006;Hebert, Dubois, Wolfson, Chambers, & Cohen, 2001;Mensie & Steffen, 2011;Okamoto, Hasebe, & Harasawa, 2007;Park, Butcher, & Maas, 2004;Yamamoto & Wallhagen, 1998). Therefore, focusing on family caregivers and care recipients, as well as the dynamics between them, was essential to improving the framework of understanding LTC services use.…”
mentioning
confidence: 99%
“…Tamiya et al (2011) shared the same sentiment as the studies presented above. Mensie and Steffen (2011) who applied the Andersen Model to variable selection in their studies, reported that there is a lack of relationship between caregiver depression and 3-month respite usage.…”
Section: Aim Of Thesismentioning
confidence: 99%